Jennifer is buying cupcakes for a party. 12cupcakes is $8.40. What is the unit rate for
each cupcake?

Answers

Answer 1
Answer:

Answer:

24

Step-by-step explanation:

Answer 2
Answer:

Final answer:

The unit rate for each cupcake is $0.70.

Explanation:

To find the unit rate, we need to divide the total cost by the number of cupcakes. In this case, Jennifer bought 12 cupcakes for $8.40. So, the unit rate is $8.40 divided by 12 cupcakes.

We can calculate it as:

Unit rate = Total cost / Number of cupcakes = $8.40 / 12 cupcakes

Simplifying the division, we get:

Unit rate = $0.70 per cupcake

Learn more about Unit Rate here:

brainly.com/question/11258929

#SPJ2


Related Questions

Tommy and his dad rode their bikes at a speed of 12 m.h.p. For 2 hours. They rested in a park and rode at 8 m.p.h. For 2 more hours. How many miles did they travel in total?
(2+2)^5 + (8+3)^5 Divided by 10?
guests at a party are seated at 3 tables. small table has 5 seats and 2 pizzas. medium table has 7 seats and 3 pizzas. the large table has 12 seats and 5 pizzas. which table gets most pizza?
Solve equation for the given variable 7x + 18 = -24
The number of grocery items on two grocery lists differs by 7. the total number of items is 33. How many items are on each list?

32% of 25 pages in percent

Answers

32% or 25 is 8 
Converting percentage to a decimal: 
32% = 32 / 100 = 0.32 

What is 32% of 25 
= 32% * 25 
= 0.32 * 25 
= 8
32 \% = .32\nMultiply\n.32 * 25 = 8\n\boxed 8

PLEASE HELP ASAP 25 PTS + BRAINLIEST TO RIGHT/BEST ANSWER

Answers

Answer:

(-6,9,-3)

Step-by-step explanation:

-3x -y +z=6

-3x-y+3z =0

x-3z =3

Multiply the second equation by -1

-1 *(-3x-y+3z) =0*-1

3x +y -3z =0

Add this to the first equation

-3x -y +z=6

3x +y -3z =0

----------------------

0 + 0 + -2z = 6

Divide by -2

-2z/-2 = 6/-2

z = 6/-2

z=-3


Take the third equation to find x

x-3z=3

x-3(-3) = 3

x+9=3

Subtract 9 from each side

x+9-9 =3-9

x=-6

Now we need to find y

3x +y -3z =0

3(-6) +y -3(-3) =0

-18 +y +9=0

-9+y =0

Add 9 to each side

-9+9+y = 0+9

y=9

(-6,9,-3)

\left\{\begin{array}{ccc}-3x-y+z=6\n-3x-y+3z=0\nx-3z=3&|\text{add 3z to both sides}\end{array}\right\n\nx=3+3z\n\n\text{Substitute it to the first and the second equation:}\n\n\left\{\begin{array}{ccc}-3(3+3z)-y+z=6\n-3(3+3z)-y+3z=0\end{array}\right\n\n\text{use distributive property}\n\n\left\{\begin{array}{ccc}-9-9z-y+z=6&|\text{add 9 to both sides}\n-9-9z-y+3z=0&|\text{add 9 to both sides}\end{array}\right\n\n\text{combine like terms}

\left\{\begin{array}{ccc}-8z-y=15\n-6z-y=9&|\text{change the signs}\end{array}\right\n\n\underline{+\left\{\begin{array}{ccc}-8z-y=15\n6z+y=-9\end{array}\right}\qquad\text{add both sides of the equations}\n.\qquad-2z=6\qquad\text{divide both sides by (-2)}\n.\qquad\boxed{z=-3}\n\n\text{Put the value of z to the second equation:}\n\n6(-3)+y=-9\n-18+y=-9\qquad\text{add 18 to both sides}\n\boxed{y=9}\n\n\text{Put the value of z to the equation}\ x=3+3z:\n\nx=3+3(-3)\nx=3-9\n\boxed{x=-6}

Answer:\ \boxed{x=-6,\ y=9,\ z=-3\to(-6,\ 9,\ -3)}

Miley music has a sale on music CDs all music CDs are discounted 15% Marianas receipt indicates that she saved $3 on her CD purchase what is the full price of her music CD before the discount

Answers

Answer: The original price of her music CD before discount is $20.

Step-by-step explanation:

Let x be the original price of her music CD.

Discount rate = 15%

At discount she saved = $3

So, According to question, our equation becomes

15%x= 3

0.15x= 3

x=$20

Hence, the original price of her music CD before discount is $20.

If x is the price before a sale
x-0.15x=x-3
0.85x=x-3
3=0.15x
x=20

The original price is $20

A ball is thrown upward from the top of a building. The function below shows the height of the ball in relation to sea level, f(t), in feet, at different times, t, in seconds:f(t) = −16t^2 + 48t + 100

The average rate of change of f(t) from t = 3 seconds to t = 5 seconds is _____feet per second.

Answers

f(x)=-16t^(2) +48t+100
Average rate of change from t = 3 to t = 5 = (f(5)-f(3))/(5-3)= (( -16(5^(2))+48(5)+100)-(-16(3^(2))+48(3)+100))/(2)= ((-16(25)+240+100)-(-16(9)+144+100))/(2)=((-400+240+100)-(-144+144+100))/(2)= (-60-100)/(2)=(-160)/(2)=-80

if the wheel(w) at the end of the arm is 105m from the spindle point(c) .what distance does this wheel cover in one full rotation of the arm?

Answers

Hello,

the length of the circomference is 2*π*radius
=2*π*105=659,7344572538565800771551104887... (m)

(X+16) (4X-6)

X=

4X=

Answers

Answer:x=0

Step-by-step explanation:Distribute

Distribute

Distribute

Combine like terms

Move terms to the left side

Combine like terms

Common factor

Find one factor